Evaluation of Japanese people's perception of risk information for making decisions to receive influenza and rubella vaccinations - Natsuko Yasuhara; Sawako Okamoto; Miki Hamada; Keita Uehara; Naoya Obana; Tomoaki Imamura (Wiley, 2021)
Abstract Background Generally, vaccination uptake in Japan lags behind World Health Organization targets. Objective This study aimed to understand how risk information and advice affect intention to receive vaccinations. Methods This study had a within‐subjects design. An online survey based on the Health Belief Model was sent to 2501 Japanese individuals (≧20 years) to assess the intention to be vaccinated for influenza and rubella after receiving minor and severe risk information and hypothetical advice about each vaccine. Regression analysis was used to measure changes in intentions to receive each vaccination after being provided with (1) risk information about each vaccine and (2) hypothetical encouragement and discouragement to be vaccinated. Main Outcomes The main outcomes included changes in vaccination intentions from baseline. Results Forty‐one percent (N = 1030) of those sent the survey completed it. At baseline, 43% and 65% of the respondents intended to have influenza and rubella vaccinations, respectively. Being provided with information about severe risks and susceptibility increased the intention to have the influenza vaccination among females in their 40s. Receiving inaccurate and discouraging information from one's mother significantly decreased the intention to have the rubella vaccination. Women 50 and older were more likely to intend not to have vaccination for rubella. Severe risk information decreased rubella vaccination intention in all age groups, except women in their 30s and 40s (p < .05). Conclusion For both vaccinations, older individuals demonstrated vaccine hesitancy. This group requires tailored messaging to help them understand their vulnerability (to influenza) and their role in transmission (for rubella) to encourage uptake of essential vaccinations. Patient or Public Contribution Members of the Japanese public responded to our online questionnaire on vaccination risk.